PERBANDINGAN NILAI Q GERD PASIEN BPJS RAWAT JALAN YANG MENDAPAT TERAPI ANTASIDA DAN OMEPRAZOL DENGAN ANTASIDA DAN LANZOPRAZOL DI KLINIK PRATAMA X SIDOARJO - Purwati, Ely; Priyoherianto, Andri; Safitri, Rifdah Atikah (Universitas Muhammadiyah Gresik, 2025)
Introduction: Gastroesophageal Reflux Disease (GERD) is a digestive tract disorder characterized by repeated reflux of stomach contents into the esophagus, causing various symptoms such as heartburn, regurgitation, heartburn, and sleep disorders. The prevalence of GERD throughout the world ranges from 15%-25%, with an increasing trend in several countries including Indonesia. Objective: This study aims to compare the Q value of GERD for outpatient BPJS patients who received combination therapy with antacid + PPI drugs [Omeprazole or lanzoprazole]. Method: This research uses a descriptive research type using a cross sectional research design, evaluated with the GERD-Q Questionnaire. Results: The results in this research are that the drugs used for GERD therapy are PPI and antacids based on research results showing that this therapy can effective in reducing the symptoms of gerd experienced by patients, the combination of antacid + lansoprazole/omeprazole + antacid is very effective in reducing the Q value of gerd from statistical data showing that the reduction between the 2 combinations is not significantly different P<0. Conclusion: The average decrease in the Q value of GERD for outpatient BPJS patients who received antacid + omeprazole, and antacid +lansoprazole therapy at the Pratama X Sidoarjo clinic was 7.25, and 9.875.